2017
DOI: 10.1113/ep086416
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training dose differentially alters muscle and heart capillary density and metabolic functions in an obese rat with metabolic syndrome

Abstract: What is the central question of this study? Regular exercise is recommended as a non-pharmacological approach for the prevention and treatment of metabolic syndrome. However, the impact of different combinations of intensity, duration and frequency of exercise on metabolic syndrome and microvascular density has not been reported. What is the main finding and its importance? We provide evidence on the impact of aerobic exercise dose on metabolic and microvascular alterations in an experimental model of metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 45 publications
(80 reference statements)
1
39
0
Order By: Relevance
“…This was reported by Farkas and colleagues who described a 10 to 20 mmHg increase in systolic blood pressure at 24 h after 2VO, persisting for up to 9 weeks [4]. Physical training, particularly aerobic exercise, has been shown to be an effective non-pharmacological therapeutic approach in the reduction of blood pressure in models of metabolic syndrome [35] and hypertension [36]. A normalization in systolic blood pressure was observed in our 2VO model after 12 weeks of moderate exercise compared to animals that were sedentary for this period.…”
Section: Discussionmentioning
confidence: 69%
“…This was reported by Farkas and colleagues who described a 10 to 20 mmHg increase in systolic blood pressure at 24 h after 2VO, persisting for up to 9 weeks [4]. Physical training, particularly aerobic exercise, has been shown to be an effective non-pharmacological therapeutic approach in the reduction of blood pressure in models of metabolic syndrome [35] and hypertension [36]. A normalization in systolic blood pressure was observed in our 2VO model after 12 weeks of moderate exercise compared to animals that were sedentary for this period.…”
Section: Discussionmentioning
confidence: 69%
“…In humans, environmental factors including early life stress [3][4][5], poor diet [16,17], and low activity level [34][35][36] increase one's risk to develop the MetS. Many pre-clinical studies have investigated the influence that HFS diet [37][38][39][40] and exercise [31,41,42] have on the development of obesityrelated MetS, while only a few have investigated the impact of early life stress [14,15]. To our knowledge, this is the first study to combine early life stress, exercise, and diet to evaluate outcomes related to this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise plays an important role in improving lipid metabolism disorders, and is increasingly seen as an adjunctive therapy for the prevention and treatment of NAFLD (16, 17, 42). Machado MV et al showed that exercise intensity would be more effective in improving metabolic parameters than frequency or duration (43). A retrospective study indicated that moderate and vigorous intensity physical activity yielded similar health benefits to low, in terms of the measured body adiposity and serum TG (38).…”
Section: Discussionmentioning
confidence: 99%